Traceback of the Psoroptes outbreak in British Columbian bighorn sheep (Ovis Canadensis). (April 2021) - Hering, Adam M.; Chilton, Neil B.; Epp, Tasha; Schwantje, Helen M.; Cassirer, Frances; Walker, Andrew; McLean, Craig; Thampy, Prasobh Raveendran; Hanak, Eryn; Wolff, Peregrine; Drew, Mark; Bardsley, Katherine D.; et al.
Abstract: Psoroptes are a non-burrowing, ectoparasitic, mange-causing mite that has been documented in American bighorn sheep populations throughout the 19th and 20th centuries; however, it was not seen on Canadian bighorn sheep until 2006. The aim of this study was to determine the potential source of the Psoroptes outbreak in Canadian bighorn sheep. Morphological and molecular analyses were used to compare mites recovered from outbreak-associated bighorn sheep, pet rabbits in Canada, and on historically infested bighorn sheep in the USA. The results revealed that Psoroptes acquired from the Canadian and outbreak-associated American bighorn sheep were morphologically more similar to those collected from rabbits than mites on historically infested bighorn sheep. Outer opisthosomal setae lengths measured an average of 81.7 μm (±7.7 μm) in outbreak associated bighorn mites, 88.9 μm (±12.0 μm) in rabbit mites and 151.2 μm (±16.6 μm) in historically infested bighorn mites. The opisthosomal lobe morphology of bighorn mites in the outbreak herds was also more similar to that of rabbit mites, previously described as P. cuniculi, than historically infested bighorn mites, which match previous descriptions of P. ovis . This finding was supported by DNA sequence data of the mitochondrial cytochrome B gene. This is the first report of Psoroptes of the rabbit ecotype on bighorn sheep. The morphological and molecular data therefore support the hypothesis that the source of Psoroptes outbreak in Canadian bighorn sheep represented a disease spillover event from rabbits rather than transmission from infested American bighorn sheep populations. Graphical abstract: Image 1 Highlights: Psoroptes infestations are not host specific. Canadian bighorn Psoroptes are morphologically distinct from USA bighorn Psoroptes . Mitochondrial DNA gene CytB can be used to differentiate Psoroptes strains. The Canadian bighorn sheep Psoroptes outbreak likely came from rabbits not USA bighorns.